Labor Contracts and Business Cycles - Boldrin, Michele; Horvath, Michael (Journal of Political Economy, 1995)
This paper investigates the claim, often put forth by real business cycle proponents, that the poor performance of their models in matching real-world aggregate labor market behavior is due to the fact that observed real wage payments do not correspond to the actual marginal productivity of labor but contain an insurance component that cannot be accounted for by the Walrasian pricing mechanism. To test this idea, we dispense with the Walrasian description of the labor market and introduce contractual arrangements between employees and employers. Assuming that employees are prevented from accessing capital markets and are more risk averse than employers, we use the theory of optimal contracts to derive an equilibrium relation between aggregate states of the economy and wage-labor outcomes. This contractual arrangement is then embedded into a standard one-sector, stochastic neoclassical growth model in order to look at the business cycle implications of the contractual hypothesis. The resulting dynamic equilibrium relations are then parameterized and studied by means of standard numerical approximation techniques. The quantitative properties of our model appear to be somewhat encouraging. We have examined different contractual environments, and in all circumstances the contracts-based equilibrium performs better than standard ones with regard to the labor market variables and at least as well with regard to the other aggregate macroeconomic variables. The present paper reports only the simulation results relative to what we consider the most empirically relevant cases.